Psychophysiology in the Study of Political Communication: An Expository Study of Individual-Level Variation in Negativity Biases. (3rd April 2019) - Soroka, Stuart; Fournier, Patrick; Nir, Lilach; Hibbing, John
Abstract : The use of psychophysiological measures has been relatively common in the study of communication; there has been a recent increase in interest among political behavioralists as well. There has nevertheless been a limited body of work that uses psychophysiological measures to better understand the impact of political mass media content. This article presents the case for using psychophysiological measures to study political communication. Focusing on skin conductance, it outlines the advantages of this measure for capturing subconscious responses to media over time, second-to-second. It then presents results from recent experimental work in the United States that highlights individual-level variation in responsiveness to negative versus positive news content—variation that is correlated with measures of psychophysiological reactions to non-news content, suggesting the relevance of deep-seated predispositions in psychophysiological research on media effects.